Fatty acid profile of humpback muscle (Rhomboideus m.) from zebu breed (Nellore cattle)=Perfil lipídico de “cupim” (músculo Rhomboideus) de gado Nelore (linhagem zebuína) - Talita Kato; Elza Youssef Youssef; Fábio Augusto Garcia Coró; Mayka Reghiany Pedrão; Massami Shimokomaki (Acta Scientiarum: Technology, 2012)
The objective of this paper was to characterize the lipidic profile of the Rhomboideus muscle (humpback) present in the Nelore breed, and compare it to the Longissimis dorsi muscle (tenderloin). Male animals with 24 months of age, raised in pasture were slaughtered in a regional slaughterhouse and the Longissimus dorsi (LD) and Rhomboideus (RH) muscles were excised from the remaining of the carcass and analyzed after 24 hours refrigeration. Moisture, protein and total lipids were quantified and the fatty acid profile was analyzed. The results obtained show significant differences (p < 0.05) in the characterization between the muscles analyzed in relation to their composition. Most of the fatty acids detected were monounsaturated (MUFA), with the oleic acid (C18:1n-9) being the fatty acid with the largest amount present, with the value of 48.11% for the RH muscle and 45.58% for LD. For saturated fatty acids (SFA), palmitic acid (C16:0) were quantified in largest quantity with 25.67 and 25.19% content for RH and LD muscles, respectively. Regarding saturation, RH muscle has greater quantity of MUFA, 56.46%, but lower PUFA/SFA ratio, with 0.081. O objetivo deste trabalho foi caracterizar o perfil lipídico do músculo Rhomboideus (cupim) presente na raça Nelore e compara-lo com o músculo Longissimis dorsi (contra filé). Animais machos com 24 meses de idade, criados em pasto foram abatidos em frigorífico regional e os músculos Longissimus dorsi (LD) e Rhomboideus (RH) retirados do restante da carcaça e analisados após 24 horas de refrigeração. Foram quantificados umidade, proteína, lipídios totais e analisado o perfil de ácidos graxos. Os resultados obtidos mostraram diferenças significativas (p < 0,05) na caracterização entre os músculos analisados em relação a sua composição. A maioria dos ácidos graxos detectados foram monoinsaturados (MUFA), sendo o ácido graxo presente em maior quantidade o ácido oleico (C18:1n-9) com valor de 48,11% para o músculo RH e 45,58% para o LD. Os ácidos graxos saturados (SFA) com o ácido palmítico (C16:0) em maior quantidade com teores de 25,67 e 25,19%, para os músculos RH e LD, respectivamente. Em relação à saturação, o músculo RH tem maior quantidade de MUFA, 56,46%, mas menor razão PUFA/SFA com 0,081.